(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Assessment of soil quality by soil analysis is a valuable tool for a farm as it determines the inputs required for efficient and economical production. A proper soil test helps ensure the application of sufficient fertilizers to meet the requirements of the crop while taking advantage of the nutrients and conditions already present in the soil. Though soil pH, electrical conductivity (EC), organic matter and texture are important features that determine the fertility of the soil, quantitative information on these properties are limited. The objective of the present study was to assess the pH, EC, organic matters and texture of four selected locations around the Qatar University campus including Biology Field (BF), Science Garden (SG), Greenhouse Inside (GHI) and Greenhouse Outside (GHO). We observed significant differences in the pH, EC and organic matter contents among the four locations. The highest pH was observed in SG and lowest in GHI whereas highest EC was observed in GHI and lowest in BF. Highest organic matter was found in GHI and lowest in BF. The soil texture of the BF and SG was sandy clay while that of GHI and GHO was loamy sand. Considering all four parameters analyzed in the present study, the GHI soil was found more suitable for plant growth. Res. Agric., Livest. Fish.7(3): 403-409, December 2020